Bridging people and sound : 12th International Symposium, CMMR 2016, São Paulo, Brazil, July 5-8, 2016, Revised selected papers /: 12th International Symposium, CMMR 2016, São Paulo, Brazil, July 5-8, 2016, Revised selected papers. (2017) - Unknown
No abstract available